A Croat's View of Ottoman Bosnia: the Travelogue of Matija Mažuranić from the Years 1839-40 - Paić-Vukić, Tatjana; Čaušević, Ekrem (2008)
The travelogue by Matija Mažuranić "Pogled u Bosnu" (A look at Bosnia) is critically examined from the Ottomanist perspective. The authors question some of Mažuranić's observations attempting to determine the factors which operated in the process of shaping his impressions of Bosnian society. They conclude that it is more fruitful to approach this text as one of the documents of cultural encounters, which are the result of the interaction between cultural stereotype and personal observation, rather than approaching it as a trustworthy account of Bosnia around the middle of the nineteenth century.
Projekt MZOS
ENG